Effect of some operational factors on the efficiency of wheat milling processes - Abdel-Wahab, M. K.; El-Shazly, M. A.; Afifi, M. K.; El-Maghawry, Hend A. M. (2007)
The present study was conducted to evaluate the performance of milling process under different operational factors including feed rate, inclination angle of sieves and air suction for cleaning and feed rate and roll clearance for milling process. The obtained data showed that the proper conditions which gave high cleaning efficiency were 12 Mg/h feed rate, 12o inclination angle and 1kPa air suction, while milling process was efficient under feed rate of 9 Mg/h and roll clearance of 1.95mm for first break, 1.50mm for second break, 0.80 mm for third break, 0.75mm for fourth break and 1mm for fifth break.
Includes references.
Summary in Arabic.
1
Keywords: Grain -- Milling; Wheat -- Milling; Flour